Thyroid cancer knowledge and awareness among women in Al-Ahsa region, Saudi Arabia: A cross-sectional study - Albinsaad, Loai Saleh (International Journal of Aquatic Research and Environmental Studies, 2026)
This study aims to assess the knowledge and awareness of thyroid cancer (TC) among women in the Al-Hassa region of Saudi Arabia. TC is a common endocrine malignancy globally, ranking as the ninth most common tumor in 2020. In Saudi Arabia, TC has a prevalence of around 10% among women, making it the second most common female tumor after breast cancer. The study seeks to determine the level of understanding regarding TC and its risk factors among the target population. Methodology: Cross-sectional questionnaire-based study for females in which they live in Al-Hassa and were aged 18 and above. The data was collected by using a questionnaire. Data was analyzed using SPSS version 27.0.1.. Results: Our study involved 381 female participants from the Al-Hassa region in Saudi Arabia. Sociodemographic characteristics showed varied age distribution (28.3%: 18-24 years; 47.8%: 25-44 years; 23.9%: above 44 years), education levels (64.8%: bachelor’s degree), and healthcare utilization (46.2%: visited health centers more than twice a year). In terms of thyroid cancer detection practices, 44.9% underwent thyroid hormone analysis, while only 17.3% had ultrasound or CT scans of the thyroid gland. Factors such as age and education level were significantly associated with knowledge scores. Undertaking a thyroid hormone analysis was associated with higher knowledge scores. Age, healthcare utilization, and education level were associated with high knowledge. Conclusion: Our study provides valuable insights into the awareness of thyroid cancer among female participants in the Al-Hassa region of Saudi Arabia. The findings highlight both positive aspects and gaps in knowledge and awareness. These findings can inform the development of targeted interventions and educational programs to improve knowledge and promote early detection of thyroid cancer. Future research should consider a larger and more diverse sample, which may influence knowledge and awareness of thyroid cancer in Saudi Arabia